Potential Effect of Spirulina Extracts on Serum Iron Reduction: Possible Application in Cancer Treatment - Asker Hamadi, Azhaar; Noory Fajer, Ali (Asian Pacific Journal of Cancer Biology, 2025)
Background: Iron overload is a significant health concern that has been linked to various pathological conditions, including cancer and thalassemia. The relationship between iron overload and cancer has been extensively studied, particularly in the context of hepatocellular carcinoma (HCC) and other malignancies. Spirulina platensis is a blue-green algae that contains bioactive compounds such as carbohydrates, proteins, lipids, vitamins, omega-3, and omega-6. These compounds make spirulina a source of antioxidants. The compound, which acts as an antioxidant, is said to decrease or stop oxidative stress resulting from free radicals, which can lead to cancer and thalassemia. Spirulina has properties as an antioxidant, anticancer, anti-apoptotic, anti-inflammatory, immunomodulatory, and antiviral agent. In the present study, an attempt is made to evaluate the effect of spirulina extract as an antioxidant and anti-inflammatory agent on iron status in thalassemia patients and its possible application in cancer treatment. Materials and Methods: Fifty male patients with thalassemia, aged 5–16 years, were enrolled in this research study. The serum of these patients was treated with spirulina. Afterward, the serum levels of iron, ferritin, transferrin, TIBC, and UIBC before and after treatment were evaluated. Results: The results indicated a decrease in iron, ferritin, and transferrin saturation levels, while total iron binding capacity, unsaturated iron binding capacity, and transferrin levels were increased. Conclusion: In conclusion, the correlation between iron overload, cancer, and thalassemia presents a complex interplay of genetic, biochemical, and environmental factors. Reducing the total body iron stored is a crucial treatment goal for thalassemia and cancer.